Joseph Campbell’s functions of myth in Galway Kinnell’s The book of nightmares - Quirós García, Elizabeth (2020)
This research paper analyzes the functions of myth in Galway Kinnell’s The book of nightmares mainly utilizing the scholarly contributions of Carl Jung and Joseph Campbell. In this analysis, the quester learns about the different functions of myth in the development of individuals as well as their need to complete cycles in life that will allow them to grow emotionally and psychologically. Kinnell’s use of imagery and unpretentious motifs of everyday living are enthralling; the “dead shoes, in the new light” allow readers to lose their way to find out who they are and what they want. XXI-century Western society has rendered the rites of passage it had previously upheld primitive. In a post-globalized era and a civilization that tends to favor capitalism and consumerism, although individuals encounter rites of passage and myth on a daily basis, they may be perceived as primeval and senseless. The book of nightmares discloses rites, rites of passage, and myths for the reader to discover opportunities of learning to mature in the world